Pengaruh Arus Kas terhadap Nilai Perusahaan pada Indeks IDX-MES BUMN 17 - Tan, Fransisca (Jurnal KIAFE, 2022)
The study aims to determine and analyze the effect of cash flow from operating, investing and financing activities on company value on IDX-MES BUMN 17 index. The study was carried out using a quantitative descriptive method for the financial statements of companies indexed on IDX-MES BUMN 17. Data analysis used multiple linear regression, hypothesis testing through the T test and F test and the coefficient of determination test. The results showed that partially operating cash flow had a non-significant positive effect on firm value and investment and financing cash flows had a negative and non-significant effect on firm value. Operating cash flow, investment and financing simultaneously have a non-significant effect on company value on IDX-MES BUMN17 Index with the magnitude of the influence exerted, namely 27.4%.